An explanation of the 15-year trend and investigation of the tuberculosis cascade in Kurdistan province. (August 2022) - Veisi, Nasrollah; Sharifi, Hamid; Shahesmaeili, Armita; Ghaderi, Ebrahim; Rahmati, Shoboo
Abstract: Objective: This study's objectives were to describe the 15-year trend from 2005 to 2019 and examine the tuberculosis cascade in the Kurdistan province from 21 march 2018–20 march 2019. Methods: This retrospective study was in 2744 patients with tuberculosis from 2005 to 2019 who were registered in Kurdistan disease registration centers. For the initial evaluation of demographic data, we utilized SPSS software version 20 and excel. Additionally, to design a care cascade, we utilized draw.io software for registered patients from 21 march 2018 to 20 march 2019 . As a result, 2489 new cases of tuberculosis remained in our study. Results: The results showed that the mean of age of people with tuberculosis was 58 years and sex distribution were 1441 (57.9) female and 1048 (42.1) male. Additionally, a cascade model showed that in Kurdistan Province, an estimated 112 new cases of smear-positive pulmonary tuberculosis, of which 90% (101 people) were sent to medical facilities and underwent diagnostic testing, with 80% of these patients (81 people). Infection was identified in 81 individuals, all of whom had their diagnoses recorded in the medical database. 82% (67 patients) of the patients who were enrolled in the treatment system received access to treatment, and 65 patients, or 97 percent, experienced no recurrence for at least a year after treatment. Correct diagnosis and therapy represented the biggest gap. Conclusion: Cascade can enhance surveillance program and focus activities to better cases, diagnose, connect to care, and help TB patients survive without recurrence.